Program Pembinaan Self Esteem Melalui Rebt Bagi Remaja Awal Di Pesantren - Laudza Zulfa Nur Dipa; Ulil Amri Syafri; Ahmad Sastra (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2026)
Adolescence is a transitional period characterized by physical, emotional, and social changes. According to Abuddin Nata, adolescence is divided into two periods: early adolescence and late adolescence. Early adolescence is a developmental period generally described as corresponding to junior high school age, while late adolescence is described as approaching high school age and above. One factor influencing development during adolescence is low self-esteem. Self-esteem influences personality, social relationships, and academic achievement. This study aims to develop a self-esteem development program through REBT Rational Emotive Behavior Therapy. REBT is able to change irrational thoughts into more adaptive rational ones. Thus, it can form positive attitudes and mindsets towards oneself. The author conducted the study using the R&D Research and Development method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results of this study obtained a systematic self-esteem development program through REBT for early adolescents in Islamic boarding schools containing nine items, namely: rationale, vision and mission, description of needs, program objectives, program components, action plans, theme development, and evaluation.